Urban development type, biodiversity and the extinction of experience - Izquierdo, Lucía; Ramos-Chernenko, Anna; Jokimäki, Jukka; Tryjanowski, Piotr; Benedetti, Yanina; Díaz, Mario; Kaisanlahti-Jokimäki, Marja-Liisa; Morelli, Federico; Pérez-Contreras, Tomás; Rubio, Enrique; Sprau, Philipp; Suhonen, Jukka; et al. (Elsevier BV, 2026)
Humans currently suffer a phenomenon called the extinction of experience by which we are losing interactions with the natural world. This process, particularly worrying in urban areas and rapidly expanding, is mainly due to the lack of orientation towards nature (i.e. connection with nature) and the lack of opportunities to experience it. Urban areas vary along a gradient from compact cities with large parks separated from residential areas (land-sparing extreme of the gradient) to sprawled-design with single-family homes and gardens and street vegetation (land-sharing extreme). This gradient and its feature variables are related to differences in biodiversity levels and the way people interact with nature, thus, it is expected that this configuration will influence the extinction of experience of citizens. Our study investigates this important question by integrating sociological data (818 questionnaires) and ecological data (bird diversity) from 9 cities across Europe and carrying out structural equation models. Our results empirically support the extinction of the experience framework. We found that living in land-sparing areas, as well as areas with more green cover and larger green patches, is positively associated with time spent in nature. These findings highlight the importance of large parks in bringing urban dwellers closer to nature. Furthermore, disconnection from nature is favored by other factors such as the lack of childhood experiences or living in biodiversity-poor neighborhoods. Politicians and urban planners should consider these factors to revert the increasingly worrying extinction of experience that entails important conservation consequences.